1998
DOI: 10.1200/jco.1998.16.5.1969
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2: from molecular genetics to clinical medicine.

Abstract: Inherited susceptibility to breast cancer has been an area of intense investigation for the past 10 years. Early work focused on identifying modes of transmission, which culminated in the identification of chromosome 17q12-21 as the first human genomic region that harbored an autosomal dominant susceptibility gene for breast cancer (BRCA1) in 1990. BRCA1 was subsequently identified and was followed shortly by the identification of BRCA2. Research in the past 3 years has elucidated much about the mutation spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(97 citation statements)
references
References 19 publications
3
89
0
5
Order By: Relevance
“…BRCA1 is a tumor suppressor gene whose inactivation is associated with a high incidence of familial breast and ovarian cancer (see Blackwood and Weber, 1998), and loss of BRCA1 function also has been implicated in the development of prostate cancer (Bishop and Kiemeney, 1997). BRCA1 over-expression can inhibit cell proliferation by transactivating p21 WAF1/CIP1 in both a p53-dependent and a p53-independent manner (Thompson et al, 1995;Somasundaram et al, 1997;Ouchi et al, 1998;Zhang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 is a tumor suppressor gene whose inactivation is associated with a high incidence of familial breast and ovarian cancer (see Blackwood and Weber, 1998), and loss of BRCA1 function also has been implicated in the development of prostate cancer (Bishop and Kiemeney, 1997). BRCA1 over-expression can inhibit cell proliferation by transactivating p21 WAF1/CIP1 in both a p53-dependent and a p53-independent manner (Thompson et al, 1995;Somasundaram et al, 1997;Ouchi et al, 1998;Zhang et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, both higher vascular endothelial growth factor (VEGF) levels (Blackwood and Weber, 1998;Linderholm et al, 2000) and increased microvessel density (MVD) (Weidner et al, 1991(Weidner et al, , 1992de Jong et al, 2000) are associated with a poorer prognosis. Recent microarray studies have also identified an association between the expression of genes involved in angiogenesis, such as VEGF, and poor prognosis following breast cancer (van't Veer et al, 2002).…”
mentioning
confidence: 99%
“…Both BRCA1 and BRCA2 function as tumor suppressor genes in the breast and ovary. 34,35,61 IOSE cells used in the study are thought to carry a BRCA mutation and originated from a woman with a strong family history of ovarian cancer, 34,61 The ovarian cancer cells OVCA433 had altered expression of BRCA genes, moreover, the expression of BRCA2 transcript in-frame exon 12 deletion (BRCA2D12) mRNA was also reported in these cells by Ho and coworkers. 61 4-HPR could directly affect mutant BRCA gene to suppress the ovarian carcinogenesis, which is a very important finding in this study and has significant implications for BRCArelated cancer prevention and merits further study.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian surface epithelial (OSE) cells originated from ovarian epithelial carcinomas in which women with a strong family history of ovarian carcinomas or with a mutation in one of the two known cancer suppressor genes-BRCA1 and BRCA2. 34,35 Since OSE cells are thought to be the site of origin of epithelial ovarian cancer, these cells are important to study their molecular and cellular properties compared to ovarian cancer cells to enhance our understanding of malignancy in ovarian cancer.…”
mentioning
confidence: 99%